Analysis of The Effect of Islamic Values and Practices Towards Entrepreneurial Intentions Mediated by Attitudes Towards Entrepreneurship - Muhammad THORIQ; N.I.S. PUTRI S.E. (Communications of International Proceedings, 2020)
Indonesia is a country with a majority Muslim population, which makes Islam is a religion practised by the majority of the Indonesian and it has a great potential in influencing the behavior of Muslims in Indonesia. However, the ratio of the number of entrepreneurs in Indonesia is still low, in which we argue that whether any religious values and teaching has a direct or indirect effect towards Muslim’s attitude towards entrepreneurship. This phenomenon is the driving force for this study. Furthermore, this study aims to determine the effect of Islamic values and Islamic practices on entrepreneurial intentions by mediating attitudes towards entrepreneurship. The survey was conducted on 211 Muslims who have career intentions as entrepreneurs. The study found that Islamic values have a significant positive effect on entrepreneurial intentions, either by mediating attitudes towards entrepreneurship or without a mediating role. Furthermore, this research is expected to provide benefits that can be used by parties related to religious education and entrepreneurship, in the form of a description of Islamic values that can foster a Muslim entrepreneurial attitude and intention. Further research can be carried out by limiting the generation or age group of respondents so that the results obtained can answer more specific research problems.
Keywords: Islamic values; Islamic practices; Intention; Entrepreneurship